Pengaruh Model Problem Based Learning terhadap Keterampilan Menulis Teks Eksplanasi Siswa Kelas VII MTsS Baitul Ihza Sitapus - Rianto, Doni; R, Syahrul (ARZUSIN, 2023)
There are three objectives of this research. First, it describes the skills of writing explanatory texts for class VII students of MTsS Baitul Ihza Sitapus without using a problem based learning model. Second, it describes the skills of writing explanatory texts for class VII students of MTsS Baitul Ihza Sitapus using a problem based learning model. Third, analyzing the effect of the problem based learning model on the skills of writing explanatory texts for class VII MTsS Baitul Ihza Sitapus. This type of research is quantitative research with experimental methods. Based on the data analysis, the problem based learning model was used to influence the skills of writing explanatory texts for class VII MTsS Baitul Ihza Sitapus.